TINGKAT VARIASI GENDER POSISI MANAJEMEN PUNCAK DAN KUALITAS LABA PERUSAHAAN - Putriana Kristanti (Fakultas Bisnis UKDW, 2010)
The purpose of this study is to analyze the relation of top management gender with earnings management. This study analyzes a sample made of Jakarta stock exchange-listed firms. Three models used in this study, first model to measure the gender variation, i.e. content analysis; the second model to analyze the earnings managemet, with regression analysis; and the third model to examine the relation of top management gender variation with earnings management, with corelation analysis. The result show that top management gender variation is not correlated with earnings management. Keywords: top management gender, earnings management